Negros, crioulos e mestiçados na sociedade charquenha : comércio de escravos, liberdades e mobilidades sociais em La Plata (Sucre), nos séculos XVI e XVII - Luis Gustavo Molinari Mundim (2022)
The conquest of the "New World" in the 16th century displaced thousands of individuals from different parts of the world to America. Spaniards, Portuguese and other Europeans from different places embarked on the adventure of exploring and getting to know a territory that, for them, was something new. In practice, this space was already inhabited by thousands of natives. In addition to the Europeans, thousands of black people, the vast majority of them Africans in the legal condition of slaves, were forcibly displaced to work in those lands, serving in different activities. The mutual influence between these groups created an essentially mixed world, the result of social, cultural and biological interactions between these people. Guided by the dynamics of miscegenation, these relationships brought into contact different experiences and worldviews that were often marked by conflict, tension and violence, but also by negotiation, overlapping and accommodation. This mixing process took place throughout Ibero-America and also in the Andean Charcas – a region that covered part of the ancient Inca empire. A territory of Quechua and Aymara-speaking peoples and the famous mines of Potosí, which became the great wealth of the Spanish Empire in the 16th and 17th centuries.Surprisingly, very little is known about the black population in the region and about their mulatto and zambo descendants, who are treated here as mestizos. Much of this silencing occurs due to a mistaken and persistent idea that, due to the altitude and the cold, black people "did not exist" in the Andes. , black people had a strong presence and werefundamental in several areas of Charquean society, notably with regard to slave labor. In the documentary surveys that we carried out in the archive of Sucre (La Plata), it was possible to verify that these black captives, in addition to many other freedmen, carried out various activities in that city, such as shoemakers, tailors, cooks, carpenters, blacksmiths, swordsmen, founders, merchants, singers; performing activities in transport, agriculture, dealing with livestock, inaddition to a dozen other trades, thus contributing to the various and dynamic historical processes that enriched that society culturally, socially and economically. Thus, in the following pages, we are dedicated to trying to fill part of this gapfound on the subject in historical studies. What we sought, after all, was to demonstrate the hypothesis that there was astrong presence of blacks and their mixed-mestizos descendants in the Charqueña region, especially in La Plata, between the years 1549 and 1700. To do so, we embarked on an investigation whose documentary base was obtained from several archives, such as those existing in Sucre, Potosí, La Paz, Lisbon and Seville, in an attempt to compare the data obtained with similar dynamic processes that occurred in other contexts. , in a movement of adjustments of macro and micro clippings. Finally, we aim to show throughout this thesis who those subjects were, their names, their life storiesand their human dimension in what was possible to reconstruct from the analyzed documentation, taking into account the dynamics of modern slavery. We also analyzed the freedom processes of hundreds of these individuals, in addition to thepresence of these blacks, creoles, morenos, mulattoes and zambos in the urban and work world, together with thesentimental relationships and sociability networks that exist there, in order to demonstrate who were active subjects and makers of Platense society.